ANALISIS MODEL PENYALURAN DANA ZIS PADA BAZNAS SUMATERA UTARA - Elizar Sinambela; Fitriani Saragih (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to identify and analyze the Zakat Funds Distribution Model, Infaq and Shadaqah on BAZNAS North Sumatra. This objective is based on conditions that exist today where an increasing number of poor people in North Sumatra. BAZNAS North Sumatra is the managing institution of zakat, infaq and sadaqah actually has the potential to be developed, which in the distribution of funds should not only consumptive, but also productive, such provision of capital on a rolling basis and also aid in the form of a tool - a tool jobs for workers. It is intended that mustahiq-sufficient. This research was conducted by analyzing the channeling of funds zakat, infaq and syadaqah that exist in today's Baznas North Sumatra. The method used is a method of research and development (R & D). Based on the results of this research note that the distribution of zakat, sadaqah infaq and conducted by BAZNAS North Sumatra is very diverse. In addition to the distribution of funds consumptive there is also productive. One of them distribute zakat, sadaqah infaq and through the "Revolving Loan Program Productive" for small business development of the poor areas of North Sumatra. In the implementation of productive revolving loan program is not supported by an adequate system so many revolving loan recipients who are not productive repay their loans. Thus the aim to elevate the status of mustahiq be muzakki yet to be achieved. Besides socialization and mentoring is also an important thing to be done by BAZNAS Sumatra. Therefore in this research and development on the Model Standard Operating Procedure for productive revolving loan. From the SOP developed a model and later in the application will be able mengembangankan small and medium enterprises so that they can also increase the recipients into giving zakat